Isolation of antibiotic-resistant strains of Staphylococcus aureus from raw milk produced by dairy cows with subclinical bovine mastitis. (Journal of Advanced Veterinary and Animal Research, 2025)
Objectives: The rise of antibiotic-resistant strains of Staphylococcus aureus in dairy milk products is a global concern, compromising treatment efficacy and highlighting the need for innovative solutions. Therefore, a study was conducted to isolate S. aureus strains (N = 21) from raw milk samples of cows infected with subclinical bovine mastitis. Additionally, the resistance of these strains against 12 different antibiotics was examined. Materials and Methods: Sixty raw cow milk samples, 20 from each of three separate dairy farms in Lahore city, were collected and screened for the presence of S. aureus. It was discovered that 70% of these milk samples were contaminated with this bacterium, indicating a widespread presence across the farms. Different isolation tests were employed in this study, including gram staining, capsule staining, catalase, mannitol salt fermentation, DNase, coagulase, and oxidase. Results: The obtained results revealed that the isolated strains of S. aureus showed % of their resistance against different antibiotics in the order of amoxicillin (85%), penicillin (71%), gentamicin (CN) (42%), carbenicillin and trimethoprim-sulfamethoxazole (33%), streptomycin, ciprofloxacin, and oxytetracycline (28%), cefotaxime (10%), and chloramphenicol (4%) in decreasing order, respectively. However, these strains showed no resistance against Bacitracin and Ampicillin. Conclusion: The existence of resistant strains of S. aureus has been attributed to various factors, such as poor milk hygiene, delayed milk transportation, subclinical bovine mastitis among dairy cows, and antibiotic-resistant genes. Thus, our present study will provide useful information about the resistant strains of S. aureus, which may transfer through cows into milk and then produce serious food-borne diseases in human beings. This study will be helpful to improve and control the quality of dairy products in Pakistan.J. Adv. Vet. Anim. Res., 12(1): 252–259, March 2025http://doi.org/10.5455/javar.2025.l892